2011
DOI: 10.1371/journal.pone.0021795
|View full text |Cite
|
Sign up to set email alerts
|

Association of Age with Mortality and Virological and Immunological Response to Antiretroviral Therapy in Rural South African Adults

Abstract: ObjectiveTo assess whether treatment outcomes vary with age for adults receiving antiretroviral therapy (ART) in a large rural HIV treatment cohort.DesignRetrospective cohort analysis using data from a public HIV Treatment & Care Programme.MethodsAdults initiating ART 1st August 2004 - 31st October 2009 were stratified by age at initiation: young adults (16–24 years) mid-age adults (25–49 years) and older (≥50 years) adults. Kaplan-Meier survival analysis was used to estimate mortality rates and age and person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

24
109
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(137 citation statements)
references
References 48 publications
24
109
4
Order By: Relevance
“…Some authors reported, as in our study, that older patients presented with slower immune reconstitution in the short term, six months after ARVT initiation [3,5,[10][11][12]. This may be explained by a lower thymic output of CD4 cells in the elderly [2,13].…”
Section: Discussionsupporting
confidence: 66%
“…Some authors reported, as in our study, that older patients presented with slower immune reconstitution in the short term, six months after ARVT initiation [3,5,[10][11][12]. This may be explained by a lower thymic output of CD4 cells in the elderly [2,13].…”
Section: Discussionsupporting
confidence: 66%
“…21 A study of *9,000 adults on ART in South Africa found lower rates of virologic suppression in younger adults (16-24 years) compared with those aged 25-49 years. 22 These data suggest that younger age predicts failure to achieve viral suppression and that this risk decreases with age. Younger age is associated with poor ART adherence.…”
Section: Discussionmentioning
confidence: 86%
“…7 Most studies on ART retention have reported on adults, with adolescents included within the adult age group, making it difficult to extract information specific to adolescents. [8][9][10][11] Emerging evidence suggests that adolescents are falling behind in HIV care compared to adults as a result of not receiving specialised attention and services. 12,13 A study performed in seven African countries, excluding Zimbabwe, showed that adolescents and young adults combined (age 15-24 years) had higher rates of loss to follow-up (LTFU) and higher mortality compared with older adults (age 50 years).…”
mentioning
confidence: 99%
“…A systematic search for publications on ART outcome studies in PubMed, Cochrane Database, Google Scholar and ClinicalTrial.gov, comparing younger vs. older adolescents and younger vs. older adults, showed that with respect to ART retention, adolescents (age 10-19 years) were often misclassified as adults aged 15 years, 8,9 16 years 11 or 18 years. 10 No studies reported attrition rates within the adolescent age group or between younger and older adults.…”
mentioning
confidence: 99%